Sensitivity Analysis in the Design of the Establishment of Mosaccha Tempe Agroindustry in Bandar Lampung - Wicaksana, Bayu; Melatiningsih, Atri; Rizal, Samsul; Hidayati, Sri; Kustyawati, Maria Erna; Endaryanto, Teguh (Jurnal Bio-Geo Material Dan Energi, 2026)
Mosaccha tempeh is a fermented soybean product produced using Rhizopus oligosporus as a starter culture with the addition of Saccharomyces cerevisiae, and it has strong development potential. This study conducted financial and sensitivity analyses to evaluate the feasibility of establishing a Mosaccha tempeh agroindustry and its responsiveness to changes in key variables affecting business viability. The research aimed to assess the impact of various scenarios on business feasibility. The methods employed included surveys, observations, and interviews using a purposive sampling technique. Premium tempeh producers in Bandar Lampung were selected as prototypes, with UMKM Tempeh Cap Mobil serving as a reference to align the data with current conditions. Data were processed using Microsoft Excel and analyzed under several scenarios: increases in raw material prices (10%, 20%, and 30%), decreases in selling prices (10%, 20%, and 30%), and combinations of both factors at the same percentage levels. Under normal assumptions, the establishment of a Mosaccha tempeh agroindustry in Bandar Lampung is considered feasible, with an NPV of Rp 2,450,599,432.50, an IRR of 76%, a B/C ratio of 1.49, and a payback period of 1.67 years. Sensitivity analysis results indicate that increases in raw material costs of up to 30%, decreases in selling prices of up to 20%, and a combined 10% increase in raw material costs with a 10% decrease in selling prices do not significantly affect feasibility. However, simultaneous increases in raw material prices and decreases in selling prices are the most sensitive factors influencing the financial viability of the Mosaccha tempeh agroindustry in Bandar Lampung.